2013
DOI: 10.1038/cddis.2013.200
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide N-methyltransferase expression in SH-SY5Y neuroblastoma and N27 mesencephalic neurones induces changes in cell morphology via ephrin-B2 and Akt signalling

Abstract: Nicotinamide N-methyltransferase (NNMT, E.C. 2.1.1.1) N-methylates nicotinamide to produce 1-methylnicotinamide (MeN). We have previously shown that NNMT expression protected against neurotoxin-mediated cell death by increasing Complex I (CxI) activity, resulting in increased ATP synthesis. This was mediated via protection of the NDUFS3 subunit of CxI from degradation by increased MeN production. In the present study, we have investigated the effects of NNMT expression on neurone morphology and differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 49 publications
2
61
0
Order By: Relevance
“…Furthermore, a recent study showed that NNMT overexpression was associated with increased radioresistance via regulating nicotinamide metabolism [22]. And Parsons et.al have found that NNMT expression reduced cell death by increasing ATP synthesis and complex I activity [23], and was able to induce changes in cell morphology via ephrin-B2 and Akt signaling in human neuroblastoma cells [24]. And very recently, a study found NNMT depletion induced cell apoptosis via mitochondria-mediated pathway in human breast cancer cells [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent study showed that NNMT overexpression was associated with increased radioresistance via regulating nicotinamide metabolism [22]. And Parsons et.al have found that NNMT expression reduced cell death by increasing ATP synthesis and complex I activity [23], and was able to induce changes in cell morphology via ephrin-B2 and Akt signaling in human neuroblastoma cells [24]. And very recently, a study found NNMT depletion induced cell apoptosis via mitochondria-mediated pathway in human breast cancer cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…Win et al [17] observed that NNMT overexpression was positively correlated with Akt phosphorylation and implied worse prognosis in patients with nasopharyngeal carcinoma. Thomas et al [24] found NNMT expression regulated neuron morphology in vitro via the sequential activation of the EFNB2 and Akt cellular signaling pathways. And very recently Zhang et al [25] reported phosphorylation of Akt and ERK 1/2 was decreased in NNMT shRNA treated human breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, natural product methyltransferases (NPMTs) comprise a diverse group of enzymes that frequently transfer methyl groups to small molecules from SAM as the methyl donor. Many NPMTs, including NNMT, are specifically expressed in nervous system tissues, and defects in function are associated with neurological disorders (summarized in Supplemental Figure 1A) (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). We interrogated the relative expression levels and prognostic significance of 11 NPMTs in the 2 largest GBM datasets, TCGA and REMBRANDT.…”
Section: Gbms Overexpress Nicotinamide (Nam) N-methyltransferase (Nnmt)mentioning
confidence: 99%
“…SH-SY5Y human neuroblastoma, which do not endogenously express NNMT, and S.NNMT.LP human neuroblastoma, comprising SH-SY5Y stably expressing NNMT Cterminally tagged to the V5 epitope (NNMT-V5) and produced as part of our ongoing studies [10,11,20], were cultured as previously described. Although SH-SY5Y do not represent a differentiated neurone-like model, they do exhibit pan-neuronal characteristics, express many neuronal markers such as synaptophysin and are readily amenable to genetic manipulation [10,20].…”
Section: Cell Culturementioning
confidence: 99%